37.8k views
1 vote
Solve 4(x-3 )+x =2x+9 and justify your solution

User Abb
by
4.8k points

2 Answers

6 votes
X=7
after you remove parentheses you do those steps
Solve 4(x-3 )+x =2x+9 and justify your solution-example-1
User Ajit Satarkar
by
4.8k points
4 votes

Answer:

X=7

Explanation:

Multiply your 4 out on the left side to get

4x-12+x=2x+9

combine like terms on left side

5x-12=2x+9

get the x's by them selves

3x=21

divide both sides by 3

x=7

hope this helps

User Flapjack
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.